Varicella and Stroke - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
Four cases of cerebrovascular disease following varicella infection are reported from the Giannina Gaslini Children's Hospital and Research Institute, Genoa, Italy.